2014
DOI: 10.1161/circep.114.001796
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Storm Induced by Cardiac Resynchronization Therapy Is Determined by Pacing on Epicardial Scar and Can be Successfully Managed by Catheter Ablation

Abstract: Background-The mechanism of cardiac resynchronization therapy (CRT)-induced proarrhythmia remains unknown. We postulated that pacing from a left ventricular (LV) lead positioned on epicardial scar can facilitate re-entrant ventricular tachycardia. The aim of this study was to investigate the relationship between CRT-induced proarrhythmia and LV lead location within scar. Methods and Results-Twenty-eight epicardial and 63 endocardial maps, obtained from 64 CRT patients undergoing ventricular tachycardia ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 18 publications
3
54
0
6
Order By: Relevance
“…Pacing in the presence of an infarct scar has also been reported to cause an electrical storm (Roque et al . ). Further, it can accelerate the progression of heart failure and increase mortality (Wilkoff et al .…”
Section: Discussionmentioning
confidence: 97%
“…Pacing in the presence of an infarct scar has also been reported to cause an electrical storm (Roque et al . ). Further, it can accelerate the progression of heart failure and increase mortality (Wilkoff et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been reported that pacing in myocardial scar leads to a prolonged and fQRS . Furthermore, electrical storms, which are related to pacing on epicardial scar, also have been reported . Therefore, the LV lead on the lateral wall might have been on an LV free wall scar in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Roque et al 1 present their data on CRT-induced proarrhythmia because of pacing from within, or adjacent to, an epicardial scar demonstrated on cardiac MRI (cMRI). The authors demonstrate that this phenomenon can be successfully managed with catheter ablation and that in most cases CRT can be restored after ablation.…”
Section: Current Studymentioning
confidence: 99%